Early weight gain in infants with Robin sequence after mandibular distraction. Issue 10 (October 2022) - Harris, J.A.; Hashim, E.; Larson, K.; Caprio, R.M.; Gordon, A.M.; Resnick, C.M.
Abstract: This retrospective cohort study was performed to assess weight gain in infants with Robin sequence (RS) treated by mandibular distraction osteogenesis (MDO). The primary outcome variable was average daily weight gain for the following time periods: (1) birth to MDO (T1), (2) MDO to distractor removal (T2), (3) distractor removal to 6 months later (T3), and (4) 6 months to 12 months following distractor removal (T4). Published growth curves were used for comparison. Differences were assessed using the Wilcoxon matched-pairs signed rank test. Twenty-two infants were included in the study. During T1, the infants had 9.47 ± 12.61 g/day less weight gain than expected ( P = 0.001). However, for T2, T3, and T4, the infants demonstrated 3.48 ± 6.17 g/day ( P = 0.028), 2.19 ± 4.47 g/day ( P = 0.030), and 1.83 ± 3.25 g/day ( P = 0.028) more weight gain than expected. Feeding tube use resulted in improved weight gain during T1 ( P < 0.001), but was associated with poorer weight gain in T3 ( P = 0.003) and T4 ( P = 0.001). In conclusion, infants with RS treated by MDO demonstrated poorer weight gain relative to their peers between birth and the MDO operation. However, from the MDO procedure to 12 months post-distractor removal, infants who had MDO showed faster weight gain than their age-matched peers.